Insecticidal activity of essential oil from seeds of Poncirus trifoliata (L.) Raf. - Rahman, Atiqur; Siddiqui, Shah Alam; Rahman, M Oliur; Kang, Sun Chul (Bangladesh Journal of Botany, 2018)
The essential oil from the seeds of oriental medicinal plant Poncirus trifoliata (L.) Raf. was tested for repellent and fumigant efficacy on fruit fly (Drosophila melanogaster) and mosquito (Anopheles culicifacies). The oil showed potent activity with 76.2 and 93.2% mortality in fumigant assay, and 77.1 and 93.2% repellent efficacy on fruit fly at doses of 100 and 200 μg/ml, respectively. The application of oil against mosquito showed 80.0% mortality in fumigant assay and 70.3% repellency at 100 μg/ml dose. Thus, essential oil of P. trifoliata seeds can be considered as a potential source of biologically active compounds for pest control.